Effects of low-, medium-, and high-oil dried distillers grains with solubles on growth performance, nutrient digestibility, and fat quality in finishing pigs - A B Graham; Robert D Goodband; Michael D Tokach; Steven S Dritz; Joel M DeRouchey; Sureemas Nitikanchana; J J Updike (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 1,480 pigs were used in 3 experiments to determine the effects of dried distillers grains with solubles (DDGS) varying in oil content on growth performance, carcass characteristics, carcass fat quality, and nutrient digestibility in growing-finishing pigs. In Exp. 1, 1,198 pigs (PIC 337 × 1050, initially 101.6 lb) were used to evaluate the effects of corn DDGS with 5.4 or 9.6% oil (as-fed). Pigs were allotted to a cornsoybean meal—based control diet or diets with 20 or 40% of the two DDGS sources. From d 0 to 82, ADG was unaffected by DDGS source or level. Increasing 5.4% oil DDGS made F/G poorer (linear, P<0.01), whereas F/G did not change for pigs fed 9.6% oil DDGS. Regardless of DDGS source, carcass yield and HCW decreased (linear, P<0.04) with increasing DDGS. Increasing DDGS increased jowl iodine value (IV), but the magnitude was greater in pigs fed the 9.6% oil DDGS compared with those fed 5.4% oil DDGS (DDGS source × level interaction; P<0.01). In Exp. 2, a total of 270 pigs (PIC 327 × 1050, initially 102.5 lb) were allotted a corn-soybean meal—based control diet with 20 or 40% of a 9.4% oil or 12.1% oil DDGS. From d 0 to 75, ADG increased for pigs fed increasing 9.4% oil DDGS but not for pigs fed 12.1% oil DDGS (quadratic interaction, P<0.02). Increasing DDGS increased (linear, P<0.01) jowl IV and tended (linear, P<0.07) to improve F/G. Regardless of source, HCW and carcass yield decreased (linear, P<0.05) as DDGS increased. In Exp. 3, nutrient digestibility of the 4 DDGS sources was determined using pigs fed either a corn-based basal diet or a DDGS diet with 50% basal diet and 50% DDGS. On an as-fed basis, corn contained 1,756 and 1,594 kcal/lb GE and DE, respectively. The 5.4, 9.6, 9.4, and 12.1% oil DDGS contained 1,972, 2,108, 2,142, and 2,224 kcal/lb (as-fed) GE and 1,550, 1,674, 1,741, and 1,694 kcal/lb DE, respectively (as-fed). Stepwise regression indicated that the oil (ether extract) content was the only significant variable in explaining differences in energy content, and that a 1% change in oil content will change the DE by 28 kcal/lb (Adjusted R2 = 0.41) and NE by 52 kcal/lb (Adjusted R2 = 0.86; as-fed).; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; DDGS; Digestibility; Growth performance; Finishing pig; Iodine value